System analysis and test-bed for an atmosphere-breathing electric propulsion system using an inductive plasma thruster. (June 2018) - Romano, F.; Massuti-Ballester, B.; Binder, T.; Herdrich, G.; Fasoulas, S.; Schönherr, T.
Abstract: Challenging space mission scenarios include those in low altitude orbits, where the atmosphere creates significant drag to the S/C and forces their orbit to an early decay. For drag compensation, propulsion systems are needed, requiring propellant to be carried on-board. An atmosphere-breathing electric propulsion system (ABEP) ingests the residual atmosphere particles through an intake and uses them as propellant for an electric thruster. Theoretically applicable to any planet with atmosphere, the system might allow to orbit for unlimited time without carrying propellant. A new range of altitudes for continuous operation would become accessible, enabling new scientific missions while reducing costs. Preliminary studies have shown that the collectible propellant flow for an ion thruster (in LEO) might not be enough, and that electrode erosion due to aggressive gases, such as atomic oxygen, will limit the thruster lifetime. In this paper an inductive plasma thruster (IPT) is considered for the ABEP system. The starting point is a small scale inductively heated plasma generator IPG6-S. These devices are electrodeless and have already shown high electric-to-thermal coupling efficiencies using O 2 and CO 2 . The system analysis is integrated with IPG6-S tests to assess mean mass-specific energies of the plasma plume and estimate exhaust velocities. Highlights: Collect and use planet's atmosphere as propellant for an electric thruster. Compensate drag of satellites at very low altitudes to extend life time. Inductive plasma thruster: electrodeless device to avoid electrode erosion. First thrust estimation using a small-scale inductively heated plasma generator. Results show feasibility of drag compensation for such a system.